English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

(6)/y+2- (3/y)=1

2007-05-22 12:43:19 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

5 answers

Assuming the first part is 6/(y+2) and not (6/y) + 2, then multiply both sidex by y(y+2). This will make it much easier to solve.

6y(y+2)/(y+2) - 3y(y+2)/y = y(y+2)
6y - 3(y+2) = y(y+2)
6y - 3y + 6 = y^2 + 2y
3y + 6 = y^2 + 2y
y^2 - y - 6 = 0
(y + 2)(y - 3) = 0
So y = -2, 3

2007-05-22 12:47:24 · answer #1 · answered by Anonymous · 0 0

I'm guessing that you mean
6/(y+2)-3/y=1 multiply both sides by y(y+2)
6y-3(y+2)=y^2+2y
6y-3y-6=y^2+2y subtract LHS from both sides
y^2+2y-6y+3y+6=0 combine like terms
y^2-y+6=0 there are no real solutions
y=(1±√(1-24))/2
y=(1±√-23)/2
y=(1±i√23)/2

2007-05-22 20:00:37 · answer #2 · answered by yupchagee 7 · 0 0

6y - 3.(y + 2) = y.(y + 2)
6y - 3y - 6 = y² + 2y
3y - 6 = y² + 2y
y² - y + 6 = 0
(y - 3).(y + 2) = 0
y = - 2, y = 3

2007-05-23 02:25:00 · answer #3 · answered by Como 7 · 0 0

6/y+2-3/y=1

3/y+2=1

3/y=-1

y/3=-1
(raise both sides to -1)

y=-3

2007-05-22 19:48:43 · answer #4 · answered by AndyB 2 · 0 0

-3

Solution

6/y + 2 - 3/y = 1

xbs by y

6 + 2y - 3 = y

Collect like terms

6 - 3 = y - 2y

-3 = y

2007-05-22 19:50:51 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers